2001
DOI: 10.1128/mcb.21.4.1239-1248.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Induced Formation of Transcription Factor Complex ERSF Including NF-Y (CBF) and Activating Transcription Factors 6α and 6β That Activates the Mammalian Unfolded Protein Response

Abstract: The levels of molecular chaperones and folding enzymes in the endoplasmic reticulum (ER) are controlled by a transcriptional induction process termed the unfolded protein response (UPR). The mammalian UPR is mediated by the cis-acting ER stress response element (ERSE), the consensus sequence of which is CCAAT-N 9 -CCACG. We recently proposed that ER stress response factor (ERSF) binding to ERSE is a heterologous protein complex consisting of the constitutive component NF-Y (CBF) binding to CCAAT and an inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
191
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(207 citation statements)
references
References 28 publications
10
191
1
3
Order By: Relevance
“…It can stabilize ATF6 binding to the ERSEs of Grp78 promoters, in cooperation with other binding factors such as YY1 and NF-Y. 39,40 We found that 17b-E 2 could promote TFII-I phosphorylation and nuclear localization and enhance the Grp78 promoter activity in a dose-dependent manner in the presence of TFII-I in response to ER stress. ChIP analysis further revealed that 17b-E 2 enhanced binding of TFII-I to the Grp78 promoter in ER stress.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It can stabilize ATF6 binding to the ERSEs of Grp78 promoters, in cooperation with other binding factors such as YY1 and NF-Y. 39,40 We found that 17b-E 2 could promote TFII-I phosphorylation and nuclear localization and enhance the Grp78 promoter activity in a dose-dependent manner in the presence of TFII-I in response to ER stress. ChIP analysis further revealed that 17b-E 2 enhanced binding of TFII-I to the Grp78 promoter in ER stress.…”
Section: Discussionmentioning
confidence: 81%
“…NF-Y, YY1, ATF6 and TFII-I are four key factors that bind to the ERSEs of Grp78 promoter and subsequently promote the expression of Bip. 39,40 Therefore, we examined the expression levels of NF-Y, YY1 and ATF6 in MC3T3-E1 cells treated with or without 17b-E 2 . Unexpectedly, 17b-E 2 did not significantly change these proteins expression levels following Tg treatment (Figure 3a).…”
Section: B-e 2 Induces Phosphorylation Of Tfii-i and The Binding Ofmentioning
confidence: 99%
“…pATF6a(N) and pATF6b(N) contain a bZIP domain and bind to the ER stress response element (ERSE) consensus sequence 5 0 -CCAAT-N 9 -CCACG-3 0 as a homo-or heterodimer interacting with NF-Y trimer. 36,37 Activated Ire1a and Ire1b cleave the substrate precursor XBP-1 mRNA to mature XBP-1 mRNA by their endoribonuclease activity present in their cytosolic domains. [38][39][40] XBP-1 splicing removes a 26-nucleotide intron, which switches the open reading frames to yield its bZIP and transactivation domain.…”
Section: Transcriptional Regulation Of Chopmentioning
confidence: 99%
“…Upon ER stress ATF6 is cleaved via a process termed regulated intramembrane proteolysis (Rip), resulting in the release of the N-terminal region of ATF6 from the membrane . This fragment, carrying the basic leucine zipper and transactivation domains, is translocated into the nucleus where it activates the transcription of ER-localized molecular chaperones and folding enzymes (collectively termed ER chaperones hereafter) by directly binding to the cis-acting ER stress-response element (ERSE) present in the ER chaperone promoters, in collaboration with the general transcription factor NF-Y Yoshida et al, 1998;Yoshida et al, 2000;Yoshida et al, 2001b). Induced ER chaperones help maintain the homeostasis of the ER.…”
Section: Introductionmentioning
confidence: 99%